Molecular Analysis of Freshwater Goby (Sicyopterus sp.) from Bengkulu, Indonesia Based on Cytochrome b Mitochondrial Gene - Dian Fita Lestari; Santi Nurul Kamilah; Sipriyadi; Hengki Turnando; Muhammad Rasul Abdullah Halim; Noorhidayah Mamat (Jurnal Biodjati, 2026)
Sicyopterus (locally known as mungkus in Bengkulu) is a genus of amphidromous goby inhabiting rocky stream ecosystems and commonly utilized as a local food resource in Indonesia. Accurate species identification within this genus is important for biodiversity assessment and conservation because many Sicyopterus species exhibit high morphological polymorphism and interspecific phenotypic similarity, which often complicate morphology-based identification. This study aimed to identify Sicyopterus species from Bengkulu, Indonesia, using combined morphological and molecular approaches and to evaluate their phylogenetic relationships. A total of 30 specimens were collected from Bengkulu Utara, Bengkulu Selatan, and Kaur Regency, of which 14 representative coded samples were selected for molecular analysis. Genomic DNA was extracted using the gSYNC™ DNA Extraction Kit, followed by PCR amplification of the mitochondrial cytochrome b gene using two DNA primers, Cytb F217 and Cytb R1043. Sequence analyses were conducted in MEGA 11 using the Neighbor-Joining and Maximum Likelihood methods based on an 817 bp fragment. Phylogenetic and genetic distance analyses identified lineages associated with S. lagocephalus, S. squamosissimus, S. cynocephalus, S. parvei, and a putative S. aiensis lineage. Sample PG1 from the Padang Guci River (Kaur Regency) showed close affinity with S. parvei, whereas sample KD3 from the Kedurang River showed tentative affinity with S. aiensis. In addition, sample KD7, associated with S. squamosissimus, showed the highest genetic divergence (2.22% p-distance), suggesting substantial intraspecific variation or a distinct lineage. These findings expand current knowledge of Sicyopterus distribution in western Indonesia and highlight the importance of integrating molecular and morphological approaches to resolve taxonomic uncertainty in amphidromous gobies. Nevertheless, additional genes and morphometric analyses are still needed, particularly for the S. aiensis - S. cynocephalus lineage, because these taxa showed relatively low mitochondrial divergence and limited phylogenetic support in the present study.